Prediction of instantaneous milling force taking runout into account in peripheral milling of curved surface. Issue 1 (July 2015) - Hao, Hongyan; Wang, Baosheng; Tang, Wencheng
Abstract Prediction of milling forces in peripheral milling of curved surface with variable curvature is complex. And the complexity arises due to the effects of cutter runout. This paper presents a method to predict milling force taking runout into account. Based on the concept of linear interpolation, methods are developed to calculate the instantaneous tool position, angular position, feed direction, and corresponding machining time. Then, a new analytical model of instantaneous uncut chip thickness is derived in the presence of cutter runout by coordinate transformation. In addition, the entry/exit angles are described considering the workpiece boundary. Milling tests are carried out to verify the presented method. A good agreement between predicted results and experimental results both in variation tendency and magnitude is achieved, which shows that the presented method is efficient. Meanwhile, comparative study with the existing method from literature is made.